The sacra infantia in Medieval Hagiography - Bejczy, István (Studies in church history, 1994)
In his De civitate Dei, Augustine stated that anyone who wants to lead a good and Christian life must necessarily have lived in sin in his life up to then. It is quite conceivable that Augustine had his own course of life in mind when writing these words; he never made a secret of his own sinful youth, as is clear from the Confessiones. None the less, his statement is expressed in the form of a general rule.Many medieval saints’ lives seem to accord with Augustine’s statement. The saint repents after a life of sin and henceforth leads a model Christian life until the day of his death. Thus the eventual victory of Christianity over the forces of evil was demonstrated.However, there are also many vitae that follow a different pattern. The saint is sometimes supposed to have been perfect in every respect from childhood onward. He was born a saint rather than becoming one through a process of ‘spiritual maturation’. Stories about such precocious saints have not escaped notice in modern scholarship. Following E. R. Curtius, the phrase puer senex is sometimes used to denote the topos; in hagiography, expressions such as as quasi senex and cor gerens senile are used.